Thoracic Endovascular Aortic Repair of Esophageal Cancer-Associated Aortoesophageal Fistula: A Case Report and Literature Review - Akiko Sasaki; Hideto Egashira; Shinnosuke Tokoro; Chikamasa Ichita; Satoshi Takizawa; Toshitaka Tsukiyama; Hidemitsu Ogino; Jun Kawachi; Rai Shimoyama; Makoto Kako (Case Reports in Oncological Medicine)
Background. Thoracic endovascular aortic repair of an aortoesophageal fistula is an effective emergency treatment for patients with T4-esophageal cancer, as it prevents sudden death, and is a bridge to surgery. However, the course of unresectable malignant aortoesophageal fistula treated with thoracic endovascular aortic repair alone is not well-known. Case Presentation. We report a 67-year-old Japanese man with T4-esophageal cancer who experienced a chemoradiation-induced aortoesophageal fistula and was rescued with thoracic endovascular aortic repair. He recovered after the procedure and survived for 4 additional months with management of a mycotic aneurysm and secondary aortoesophageal fistula with the exposure of the stent graft into the esophagus. Thoracic endovascular aortic repair of aortoesophageal fistula with T4-esophageal cancer extended life for nearly an average of 4 months in the reported cases. As a postoperative complication, the exposure of the stent graft into the esophagus is rare but life-threatening; the esophageal stent insertion was effective. Conclusions. With postoperative management advances, thoracic endovascular aortic repair can improve survival and increase the quality of life of patients with T4-esophageal cancer.